2015
DOI: 10.1039/c5ra14151f
|View full text |Cite
|
Sign up to set email alerts
|

Tribological properties of nanodiamonds in aqueous suspensions: effect of the surface charge

Abstract: The sign of nanodiamond surface charge is discovered to profoundly impact friction at both nanometer and macroscopic scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…Numerous studies of nanoparticulate additives to oil-based systems have been reported in the literature, with many displaying significant improvements in macroscopic friction and wear rates [ 6 ]. Water-based suspensions have received far less attention [ 1 – 2 7 9 ]. Although the low shear strength of water is beneficial in the hydrodynamic regime of lubrication, under normal loads it also enables contact between opposing surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of nanoparticulate additives to oil-based systems have been reported in the literature, with many displaying significant improvements in macroscopic friction and wear rates [ 6 ]. Water-based suspensions have received far less attention [ 1 – 2 7 9 ]. Although the low shear strength of water is beneficial in the hydrodynamic regime of lubrication, under normal loads it also enables contact between opposing surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, their impact on the performance of existing phosphate ester anti-wear additives is unknown. Several studies of nanodiamond additives have revealed their ability to improve tribological performance in various applications as well as various lubrication regimes including boundary lubrication [11][12][13]. However, their direct influence on the performance of existing additives has not been extensively studied to date.…”
mentioning
confidence: 99%
“…The energy dissipation of the QCM that can also be related to the quality factor Q of the QCM oscillator, therefore, increases. If the QCM quality factor was Q ≈ 50,000 in air, it would drop to Q ≈ 3280 after immersion in water [7]. Since, the ratio f /R is proportional to the quality factor Q of the QCM oscillator, the relative change in Q factor can be approximated as Q/Q = (f/R)/(f/R), as shown in Figure 1d [33].…”
Section: Quartz Crystal Microbalance Data Analysismentioning
confidence: 99%
“…They are available as manufactured materials with a wide range of surface treatments and have great potential for reducing friction [5]. Reductions or increases in friction coefficients and wear associated with nanoparticles are, however, closely linked to nanoparticle concentration, size, morphology, electrical charge, and the surface treatment employed to prevent agglomeration [6,7]. Given that nanoparticles are also ubiquitous in nature in the form of wear particles resulting from frictional rubbing process [8], studies of their behavior are timely and compelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation